PENGGUNAAN KRITERIA rcP PADA PEMILIHAN PEUBAH BEBAS TERBAIK JIKA TERDAPAT MULTIKOLINEARITAS - Sugiarti, Harmi (Jurnal Matematika Sains dan Teknologi, 2007)
Some procedures can be used for selecting independent variables, one of them is the procedure of all possible regression with robust Cp (RCp) criterion. This statistic is not sensitive with multicollinearity in model and outlier residuals. The aim of this article is to investigate the use of RCp criterion in selecting independent variables. The result of the simulation experimental data shows that the RCp criterion fits enough to select independent variables.